Cultural Diplomacy between Indonesia and Timor Leste 2020-2024 - Garra Kurniawan; Ali Noer Saman (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This study analyzes the cultural diplomacy relations between Indonesia and Timor-Leste during the 2020-2024 period. Employing a qualitative approach through library research and interviews, the study finds that cultural diplomacy plays a significant role in strengthening bilateral relations based on three main findings. First, cultural diplomacy strengthens people-to-people diplomacy through arts, education, and cultural festival programs that build mutual trust between communities. Second, its impact extends to the education, economic, and political sectors, demonstrating a spillover effect from cultural cooperation. Third, its implementation faces structural obstacles such as limited financial and human resources, as well as digitalization challenges. Overall, cultural diplomacy proves to be an effective soft power instrument for historical reconciliation and enhancing multidimensional bilateral relations, although it requires strengthening institutional capacity and digital innovation.